The Effect of Acceptance and Management of Political Party Funds on the Future of Political in Indonesia - Galih Puji Kurniawan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
The aim of this article was to analyze the effect of acceptance and management of political parties in Indonesia. To understand this study's problem, study the data we have done, including reviewing ten academic findings from international publications, observing and documenting data related to this topic. After the data was collected, we were then provided with analysis, including text analysis, description, coding, and immersion results. Every text is in a language, so we use a translation application to help us understand Indonesian. To determine whether the data constitutes a valid and reliable study finding, we review it and make sure we have answered the study questions. So the results we can report that the RSD framework has become a conceptual framework for the development of research skills for academic and educational needs. The result show that The sources of revenue for political party funds in Indonesia based on Law Number 2 of 2011, come from membership fees, donations, and state assistance. However, the majority of political party funding sources come from donors, including individual donors and business entities. There are still differences in the financial structure of political parties in the law and in daily political practice, indicating that regulations that discuss party funding (Law No. 2 of 2008 and Law No. 2 of 2011) fail to encourage political parties to raise funds to meet their operational needs Keywords: Management of Political Parties, Political Parties, Political Party Fund